2016
DOI: 10.1186/s12879-016-1575-2
|View full text |Cite
|
Sign up to set email alerts
|

Gaining and sustaining schistosomiasis control: study protocol and baseline data prior to different treatment strategies in five African countries

Abstract: BackgroundThe Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) was established in 2008 to answer strategic questions about schistosomiasis control. For programme managers, a high-priority question is: what are the most cost-effective strategies for delivering preventive chemotherapy (PCT) with praziquantel (PZQ)? This paper describes the process SCORE used to transform this question into a harmonized research protocol, the study design for answering this question, the village eligibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 38 publications
0
104
0
Order By: Relevance
“…These studies were carried out by SCORE in association with local partners, and are described in greater detail elsewhere. 23 Three studies, based in Tanzania, Kenya, and Mozambique, implemented the gaining control of the schistosomiasis protocol, in which ∼150 villages with a Schistosoma prevalence ³ 25% in an eligibility screening sample of 13-to 14-year-olds were randomly assigned to one of six treatment arms corresponding to different schedules of community-wide therapy, school-based therapy (SBT), and drug holidays (Table 1). Two additional trials, based in Kenya and Côte d'Ivoire, implemented the sustaining control of the schistosomiasis protocol, in which 75 villages with a S. mansoni prevalence between 10% and 24% in an eligibility sample based on 13-to 14-year-olds were randomly assigned to one of three study arms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were carried out by SCORE in association with local partners, and are described in greater detail elsewhere. 23 Three studies, based in Tanzania, Kenya, and Mozambique, implemented the gaining control of the schistosomiasis protocol, in which ∼150 villages with a Schistosoma prevalence ³ 25% in an eligibility screening sample of 13-to 14-year-olds were randomly assigned to one of six treatment arms corresponding to different schedules of community-wide therapy, school-based therapy (SBT), and drug holidays (Table 1). Two additional trials, based in Kenya and Côte d'Ivoire, implemented the sustaining control of the schistosomiasis protocol, in which 75 villages with a S. mansoni prevalence between 10% and 24% in an eligibility sample based on 13-to 14-year-olds were randomly assigned to one of three study arms.…”
Section: Methodsmentioning
confidence: 99%
“…Between 2012 and 2016, the Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) implemented multiyear cluster randomized trials of MDA regimens with PZQ in five African countries. 23 In these trials, villages were randomly assigned to receive one of several MDA regimens, which varied in terms of the number of MDAs received during the study period and whether treatments were school-based or communitywide. The prevalence and intensity of infection in each village were assessed before each MDA during the study period, and early analyses revealed variation in the response of these measures to MDA within trials.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the location of these snail sites and Table 1 gives additional information on the habitat type and the nearest village name. As stated before, these villages were part of a larger scale SCORE project for gaining and sustaining control of schistosomiasis and as such were undergoing different mass drug administration (MDA) strategies [22]. The MDA strategy of the nearest village is also recorded in Table 1.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In part to address the unanswered questions about best methods for schistosomiasis control, the Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) was formed. 4 A primary goal of SCORE has been to identify the most effective strategies for reducing prevalence and intensity of schistosome infections in endemic areas with different initial prevalence of Schistosoma mansoni or Schistosoma haematobium through randomized trials to compare MDA frequency and target population. We conducted one of the SCORE studies in 150 villages in western Kenya with high baseline prevalence (> 25%) of S. mansoni.…”
Section: Introductionmentioning
confidence: 99%